2018
DOI: 10.13189/ujcn.2018.060201
|View full text |Cite
|
Sign up to set email alerts
|

Security Threats and Solutions in Mobile Ad Hoc Networks; A Review

Abstract: Compared to wired-infrastructure dependent networks, Mobile Ad Hoc Networks (MANETs) are more vulnerable to attacks. Because of their dynamic topology and the absence of centralized network administration, MANETs face more security threats than centralized networks. Initial literature review on MANETs' security issues indicates that while there have been attempts to identify security threats and solutions on MANETs, comprehensive reviews are very little or lacking. In an attempt to address this gap, this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For edge computing, various studies on security of several edge computing archetypes have been reported, e.g. fog computing [6][7][8][9][10], mobile edge computing [10][11][12], mobile cloud computing [13][14][15], and mobile ad-hoc cloud computing [16][17][18]. These preliminary analyses examine security threats that influence the integrity of these edge computing archetypes, together with an overview of the security procedures of defending all functions and infrastructures.…”
Section: B Related Workmentioning
confidence: 99%
“…For edge computing, various studies on security of several edge computing archetypes have been reported, e.g. fog computing [6][7][8][9][10], mobile edge computing [10][11][12], mobile cloud computing [13][14][15], and mobile ad-hoc cloud computing [16][17][18]. These preliminary analyses examine security threats that influence the integrity of these edge computing archetypes, together with an overview of the security procedures of defending all functions and infrastructures.…”
Section: B Related Workmentioning
confidence: 99%
“…Regarding the availability attack (e.g., Denial of Service (DoS)), the adversaries attempt to exhaust the bandwidth resources by disturbing or jamming the communications [122]. Attacks targeting the communication integrity try to inject false information, change the order of messages, or replay the old messages [123]. Consequently, it is essential to provide a reliable security framework for VNs to deter these cyber attacks.…”
Section: B Game Theory For Security Protection In Vnsmentioning
confidence: 99%